2021
DOI: 10.2478/geochr-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Radiofluorescence (IR-RF) of K-Feldspar: An Interlaboratory Comparison

Abstract: Infrared Radiofluorescence (IR-RF) is a relatively new method for dosimetric dating of the depositional timing of sediments. This contribution presents an interlaboratory comparison of IR-RF measurements of sedimentary feldspar from eight laboratories. A comparison of the variability of instrumental background, bleaching, saturation, and initial rise behaviour of the IR-RF signal was carried out. Two endmember samples, a naturally bleached modern dune sand sample with a zero dose and a naturally saturated samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…If we assume typical environmental dose rates of between 3 and 1 Gy ka −1 , then IR-RF dating could produce age estimates ranging from 1.2 to 3.6 Ma, which is around 4 times greater than the upper dating limit of conventional luminescence dating methods. However, more recent studies (Murari et al, 2021b;Kreutzer et al, 2022) indicated a dose saturation at around 1500 Gy, reducing the previously predicted temporal limit of IR-RF dating. Hence, the uncertainty surrounding its upper age limit remains, and further studies on known-age samples are required to assess whether the sample/grain geochemistry influences the age limit.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…If we assume typical environmental dose rates of between 3 and 1 Gy ka −1 , then IR-RF dating could produce age estimates ranging from 1.2 to 3.6 Ma, which is around 4 times greater than the upper dating limit of conventional luminescence dating methods. However, more recent studies (Murari et al, 2021b;Kreutzer et al, 2022) indicated a dose saturation at around 1500 Gy, reducing the previously predicted temporal limit of IR-RF dating. Hence, the uncertainty surrounding its upper age limit remains, and further studies on known-age samples are required to assess whether the sample/grain geochemistry influences the age limit.…”
Section: Introductionmentioning
confidence: 70%
“…A total of five samples were selected to represent a diversity of (i) geological context, (ii) geochemistry, (iii) shape of the IR-RF signal, and (iv) age. Sample Gi326 from a Triassic sandstone from Bayreuth, Germany, is composed of 89 % of K-feldspar (Sontag-González and Fuchs, 2022) and has previously been used as a reference sample in a laboratory comparison of IR-RF dating (Murari et al, 2021b). X7343 was collected from a Pliocene sediment at the Nyayanga site in the Homa peninsula, Kenya (Plummer et al, 2023).…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“…If we assume typical environmental dose rates of between 3 and 1 Gy ka −1 , then IR-RF dating could produce age estimates ranging from 1.2 to 3.6 Ma, which is around 4 times greater than the upper dating limit of conventional luminescence dating methods. However, more recent studies (Murari et al, 2021b;Kreutzer et al, 2022) indicated a dose saturation at around 1500 Gy, reducing the previously predicted temporal limit of IR-RF dating. Hence, the uncertainty surrounding its upper age limit remains, and further studies on known-age samples are required to assess whether the sample/grain geochemistry influences the age limit.…”
Section: Introductionmentioning
confidence: 70%
“…A total of five samples were selected to represent a diversity of (i) geological context, (ii) geochemistry, (iii) shape of the IR-RF signal, and (iv) age. Sample Gi326 from a Triassic sandstone from Bayreuth, Germany, is composed of 89 % of K-feldspar (Sontag-González and Fuchs, 2022) and has previously been used as a reference sample in a laboratory comparison of IR-RF dating (Murari et al, 2021b). X7343 was collected from a Pliocene sediment at the Nyayanga site in the Homa peninsula, Kenya (Plummer et al, 2023).…”
Section: Materials and Instrumentationmentioning
confidence: 99%